Tindak Tutur Asertif dalam Drama 5 Ji Kara 9 Ji Made Karya Shin Hirano - Chandrayani, Ni Made Ary Puspita; Andry Anita Dewi, Ni Made (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2021)
This study entitled Tindak tutur asertif dalam drama 5 ji kara 9 ji made karya Shin Hirano . In addition, this study is to find out the perlocutionary effect that was inflicted by the speaker towards the interlocutors through the asse rtive illocutionary act . Furthermore, this study applied a theory concerning speech act proposed by Searle (1985).  In terms of analyzing data, t he method and technique of identity method ( metode padan ) with a pragmatic approach was applied in this jurnal . T he result , that there were 19 data which were assertive utterances. The data in the form consists of 4 assertive speech data that serves to suggest, 4 assertive speech data with complaining function, 5 assertive speech data with notification function, 3 data with proud function, and 3 data with reporting function. The form of the perlocutionary effect found in interpersonal conversations is convincing, persuading, inciting, apologizing, expressing thanks, making anger, rejecting requests, mocking, and distrust.